New effective information encryption algorithms - Кінзерявий, Василь Миколайович; Гнатюк, Сергій Олександрович; Кінзерявий, Олексій Миколайович (Ukrainian Information Security Research Journal, 2012)
Two encryption algorithms were developed to improve security of electronic information resources. These algorithms based on fixed table of substitution with extended capacity and dynamic key-dependent tables of substitutions. Developed algorithms are at least two times faster than domestic encryption standard GOST 28147-2009 and practically resistant to linear and differential cryptanalysis. Properties of pseudorandom sequences generated by the proposed encryption algorithms (in counter mode) were investigated by statistical tests NIST STS and they were complex controlled by NIST STS methodic and have better results than other generators.